A.I. Yai-Yai. - MEIGS, JAMES B. (Commentary, 2023)
The article presents the discussion on enhancing personal freedom in allowing individuals for pursuing the own interests and passions. Topics include writing poems, explaining quantum physics, composing letters, writing computer code, or doing the homework; and AI being used for improving situational awareness and decision-making in a variety of contexts.